Orientasi Tata Kelola Perlindungan Dan Pemberdayaan Nelayan Kecil Di Provinsi Banten (Studi di Kabupaten Serang Dalam Masa Pandemi Covid 19) - Jumena, Mas Nana; Anom, Surya (Jurnal Komunikasi Hukum, 2021)
The relationship between fishermen and fisheries (sea) is very close, the dependence of fishermen on fish as a source of livelihood makes fish the main sector in coastal areas. Fish resources can be utilized for the greatest prosperity and welfare of the people, however the utilization of these fish resources must be carried out in a sustainable and responsible manner. This means that the utilization of fish resources must be carried out in a balanced manner and taking into account their carrying capacity and the ability of the resources to recover. During the current Covid 19 pandemic, fishermen's “fishing” activities in the Serang District of Banten Province have been disrupted, due to limited supply of fuel due to the PSBB (Large-Scale Social Restrictions), the catch is not selling well in the market or the reduced end (consumers) to the fish market . Indonesia since 2016 has had Law Number 7 of 2016 concerning the Protection and Empowerment of Fishermen, Fish Farmers and Salt Farmers, however the implementing regulations have not yet existed, so it is difficult to implement, moreover this regulation is urgently needed during a pandemic civid 19 this time.This writing is the result of an independent internal research that has been completed using legal (juridical) normative and empirical research methods (as supporting data and research arguments) carried out in the coastal area of Serang Regency.